Investigating the molecular mechanisms through which FTY720‐P causes persistent S1P1 receptor internalization. (November 2014) - Sykes, David A; Riddy, Darren M; Stamp, Craig; Bradley, Michelle E; McGuiness, Neil; Sattikar, Afrah; Guerini, Danilo; Rodrigues, Ines; Glaenzel, Albrecht; Dowling, Mark R; Mullershausen, Florian; Charlton, Steven J
<x xml:space="preserve">Abstract</x> Background and Purpose The molecular mechanism underlying the clinical efficacy of FTY720‐P is thought to involve persistent internalization and enhanced degradation of the S1P1 receptor subtype (S1P1R). We have investigated whether receptor binding kinetics and β‐arrestin recruitment could play a role in the persistent internalization of the S1P1R by FTY720‐P. Experimental Approach [3H]‐FTY720‐P and [33P]‐S1P were used to label CHO‐S1P1/3Rs for binding studies. Ligand efficacy was assessed through [35S]‐GTPγS binding and β‐arrestin recruitment. Metabolic stability was evaluated using a bioassay measuring intracellular Ca2+ release. CHO‐S1P1/3R numbers were determined, following FTY720‐P treatment using flow cytometry. Key Results The kinetic off‐rate of [3H]‐FTY720‐P from the S1P1R was sixfold slower than from the S1P3R, and comparable to [33P]‐S1P dissociation from S1P1/3Rs. S1P and FTY720‐P stimulated [35S]‐GTPγS incorporation to similar degrees, but FTY720‐P was over 30‐fold less potent at S1P3Rs. FTY720‐P stimulated a higher level of β‐arrestin recruitment at S1P1Rs, 132% of the total recruited by S1P. In contrast, FTY720‐P was a weak partial agonist at S1P3R, stimulating just 29% of the total β‐arrestin recruited by S1P. Internalization experiments confirmed that cell surface expression of the S1P1R but not the S1P3R was reduced following a pulse exposure to FTY720‐P, which is metabolically stable unlike S1P. Conclusions and Implications FTY720‐P and S1P activation of the S1P1R results in receptor internalization as a consequence of an efficient recruitment of β‐arrestin. The combination of slow off‐rate, efficacious β‐arrestin recruitment and metabolic stability all contribute to FTY720‐P's ability to promote prolonged S1P1R internalization and may be critical factors in its efficacy in the clinic.